Membedah Gagasan dalam Teks Panjang Bahasa Arab melalui Pendekatan Analisis Wacana yang Mengungkapkan Makna Tersurat dan Tersirat di Sekolah MA Zaha - Putri Nabilatus Sholeha; Ainur Rofiq Sofa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Understanding long texts in Arabic remains a significant challenge in many educational institutions, including MA Zaha. This article aims to discuss strategies for dissecting the main idea through a discourse analysis approach, focusing on both implicit and explicit meanings. This research employs a qualitative approach with a case study method, involving observation, text analysis, interviews, and documentation. The results indicate that discourse analysis aids students in identifying the main ideas that are often hidden in the form of metaphors or analogies. The application of strategies such as identifying opening paragraphs, analyzing sentence structures, contextual discussions, and idea mapping has proven effective in enhancing critical thinking, literacy, and understanding of Arab culture. This study recommends teacher training, textbook development, and the integration of cultural values to strengthen Arabic language learning holistically.